2021
DOI: 10.1111/1748-5967.12537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reference genes for miRNA expression analysis in Galeruca daurica (Coleoptera: Chrysomelidae) using qRT‐PCR

Abstract: The selection of suitable reference genes (RGs) for data normalization is a crucial step for obtaining reliable results from gene expression analysis using the quantitative real‐time polymerase chain reaction (qRT‐PCR). Expression stability of eleven putative RGs (miR‐100‐5p, miR‐92a‐3p, miR‐998‐3p, miR‐279d‐3p, miR‐305‐5p, miR‐276a‐3p, miR‐275‐3p, miR‐9a‐5p, miR‐2a‐3p, U6 snRNA and 5S rRNA) was assessed by using a web‐based tool: RefFinder, which integrates four algorithms (Delta Ct, geNorm, NormFinder, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 39 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Our data indicated that let-7-5p shows higher levels of expression in adults than any other developmental stage and lower levels in eggs. Similarly, in G. molesta and G. daurica, a higher expression in adults and lower expression in eggs were observed (Wang X.-W. et al, 2017;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Our data indicated that let-7-5p shows higher levels of expression in adults than any other developmental stage and lower levels in eggs. Similarly, in G. molesta and G. daurica, a higher expression in adults and lower expression in eggs were observed (Wang X.-W. et al, 2017;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Based on the data, we found that different programs gave disparate rankings of candidate reference gene stability under identical treatments and distinct rankings of gene stability under different treatments in an identical program. In Galeruca daurica, the best combinations of reference genes were miR-9a-5p and U6 snRNA for different stages of development, miR-305-5p and miR-100-5p for different tissue types, and miR-100-5p and miR-275-3p for various temperature settings (Wang et al, 2021). The best reference gene combinations in Helicoverpa armigera were miR-9 and U6 snRNA for stages of development, miR-305 and miR-100 for tissue types, and miR-100 and miR-92a for temperature treatments, and in Grapholita molesta, the most suitable combinations were miR-16 and U6 snRNA for the stages of development, and miR-281 and U6 snRNA for different settings of temperature (Wang X. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations